Simulation modelling of competitiveness of Ukrainian higher educational institution in Zhejiang educational market - Chen Jie (КНУБА, 2019)
Management decision-making methodology on the basis of simulation modeling is proposed in the work. A competitiveness indicators model for higher education institutions is developed. Experiments scenarios with the model for estimating and predicting competitive advantages are proposed. A number of simple simulation experiments with different values of the input parameters were performed to solve the direct simulation problem. Inverse problem solution variants by means of calibration experiments of the model are presented. The results of experimental calculations of the competitive factors impact on the university’s position in the educational services market are obtained. The possibility of making management decisions on the basis of experimental data is also shown.
Keywords: competitiveness; university; simulation; model; management decision; 005.8:378.6(477)